Caracterización anatómica cualitativa de los ejes caulinares en las especies de Piper (l.), Clado Enckea (Piperaceae) (2013)
ABSTRACT: Enckea is a clade of Piper (L.) with Neotropical distribution; it has approximately 80 species that generally show arboreal, arbustive, herbaceous, and lianescent growth habits. This clade is the only one in Piper with species living in tropical dry forests (TDF) and tropical wet forests (TWF) of Central and South America. Despite the unique distribution of Enckea and its commonness in the TDF, a detailed description of the stem anatomy of Enckea species is lacking. This information could be useful to determine the relationship between stem anatomy and habitat. Here we analyzed the stem anatomy of 25 Enckea species, looking for morphological variation in growth habits and habitat type. We found differences in vascular bundles and support tissues between arbustive and herbaceous species, as well as a clearly differentiated endodermis in some TDF species. A species distributed in Amazonian alluvian plains, Piper nudilumbum, showed aerenchyma. Despite the considerable morphological variation observed, there was no clear distinction in the stem anatomy between TDF and TWF species of Enckea.